Flexible fibers wet-spun from formic acid modified chitosan. (20th January 2016) - Li, Jinlei; Liu, Dagang; Hu, Chengming; Sun, Fengxiang; Gustave, Williamson; Tian, Huafeng; Yang, Shuguang
Highlights: Flexible chitosan fibers were wet-spun from formic acid modified chitosan. Formation of formylamide in modified chitosan was confirmed by FTIR and NMR. The crystallinity of chitosan decreased dramatically due to the modification. The maximum strain of CF fibers was 2.6 times higher than that of CA fibers. Abstract: The rigidity and low strain of chitosan fibers hindered their broader utility for biomedical applications. In present work, formic acid was employed as an efficient modifier for chitosan to prepare flexible fibers wet-spun from the formic acid modified chitosan solution. The formation of amide linkages between chitosan and formic acid was confirmed by FTIR, 13 C NMR, 1 H NMR and XRD measurements. The degree of formylation evaluated by 1 H NMR spectra was varied from 14.1% to 37.2% as a function of the reaction temperature. The results of the mechanical properties showed that the as-spun fibers exhibited an enhanced ductility with a maximum elongation at break of 21.7% compared with that spun from the chitosan dissolved in diluted acetic acid. The novel flexible chitosan fibers were anticipated to be used as comfortable wound dressing and bandages in biomedical fields.